Orientation Precision of Electron Backscatter Diffraction Measurements Near Grain Boundaries. (28th February 2014) - Wright, Stuart I.; Nowell, Matthew M.; de Kloe, René; Chan, Lisa
Abstract Electron backscatter diffraction (EBSD) has become a common technique for measuring crystallographic orientations at spatial resolutions on the order of tens of nanometers and at angular resolutions <0.1°. In a recent search of EBSD papers using Google Scholar™, 60% were found to address some aspect of deformation. Generally, deformation manifests itself in EBSD measurements by small local misorientations. An increase in the local misorientation is often observed near grain boundaries in deformed microstructures. This may be indicative of dislocation pile-up at the boundaries but could also be due to a loss of orientation precision in the EBSD measurements. When the electron beam is positioned at or near a grain boundary, the diffraction volume contains the crystal lattices from the two grains separated by the boundary. Thus, the resulting pattern will contain contributions from both lattices. Such mixed patterns can pose some challenge to the EBSD pattern band detection and indexing algorithms. Through analysis of experimental local misorientation data and simulated pattern mixing, this work shows that some of the rise in local misorientation is an artifact due to the mixed patterns at the boundary but that the rise due to physical phenomena is also observed.